INVESTIGATION OF NURSES’ COMPLIANCE WITH ISOLATıON PRECAUTIONS IN THE COVID-19 PANDEMIC - AŞKAR, Selva Ezgi; AYTEKİN KANADLI, Keriman and ÇUBUKCU, Emine and KARA SÖYLEMEZ, Gönül and SAZAK, Yasemin and ODABAŞI, Rahşan (Göbeklitepe Medical Science Journal, 2022)
In this study, it was aimed to examine the compliance of nurses with isolation precautions during the COVID-19 pandemic. A descriptive and cross-sectional study design was used. The data were collected in a university hospital between April 21 and August 1, 2020, using the "Personal Information Form" and the "Scale Compliance with Isolation Precautions" by electronic questionnaire (Google form). 109 nurses (62.4% in the 18-29 age group, 67% female, 75.2% bachelor’s degree, and 37.6% of them have a professional working period of 5-9 years) participated in the study. It was determined that the total mean score of the nurses’ compliance with isolation precautions was 80.31±13.14. There was no statistically significant difference between nurses’ scale total score averages and age, gender, previous use of isolation methods, compliance with isolation precautions, and their characteristics for the COVID-19 pandemic (The situation of receiving training on COVID-19 before starting to work in the relevant unit, following the developments regarding the COVID-19 pandemic, and having problems in applying isolation precautions while providing care to the COVID-19 patient) (p>0.05). However, it was found that the difference between the education level and the duration of working in the profession and the total score averages on the scale was statistically significant (p<0.05). Conclusion: It was determined that the level of compliance of nurses with isolation precautions was high in the COVID-19 pandemic. However, it was seen that the characteristics of the nurses for the COVID-19 pandemic and the level of compliance with the isolation precautions were not related.